2012
DOI: 10.1080/02699931.2011.570313
|View full text |Cite
|
Sign up to set email alerts
|

Does ignoring lead to worse evaluations? A new explanation of the stimulus devaluation effect

Abstract: Affective evaluation of stimuli just seen in visual search tasks has been shown to depend on task-relevant stimulus configuration (Raymond, Fenske, & Tavassoli, 2003): Whereas targets and novel stimuli were evaluated similarly, distractors were devaluated. These results were explained by an inhibition-based account of the influence of selective attention on emotion. In the present experiments, we demonstrated that stimulus devaluation might not be a consequence of attentional inhibition. By simply instructing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…could have led to a negative and positive affect encoding, respectively, since "forget"" items could be perceived as undesirable. This interpretation would be in agreement with the Evaluative coding account proposed by Dittrich and Klauer (2012). Thus, the "forget" instruction could have resulted in a general response bias and consequently participants may have given overall lower scores for those items.…”
Section: Discussionsupporting
confidence: 86%
“…could have led to a negative and positive affect encoding, respectively, since "forget"" items could be perceived as undesirable. This interpretation would be in agreement with the Evaluative coding account proposed by Dittrich and Klauer (2012). Thus, the "forget" instruction could have resulted in a general response bias and consequently participants may have given overall lower scores for those items.…”
Section: Discussionsupporting
confidence: 86%
“…However, our data did not show this pattern within a preference change effect. As pointed out in some previous studies, it could be that merely selecting or attending to an affectively neutral stimulus influences its subsequent affective evaluation even when participants make a decision unrelated to preference [29][31]. If true, some types of choice that do not seem to be directly related to preference judgment may induce preference change as well.…”
Section: Resultsmentioning
confidence: 88%
“…Put another way, one could ask: Did the image produce an emotional response, which subsequently biased word valence discrimination, or did the conceptual representations and associations produce an emotional response, which subsequently biased word valence discrimination? For instance, Dittrich and Klauer have recently suggested that the devaluation of a distractor stimulus is mediated by the affective connotation implied by the response label (what is labeled as the target) and by the instructions [46]. …”
Section: Discussionmentioning
confidence: 99%